BOOKS OF CAUCASIAN COUNTRIES IN THE MEMORIAL LIBRARY OF ANTANAS VIENUOLIS-ŽUKAUSKAS - Liepaitė, Inga (Knygotyra, 2016)
Retrospection of the memorial library of Antanas Vienuolis-Žukauskas, a native of Anykščiai, a prose writer, dramatist, apothecary, museologist, a deputy of the Supreme Council of Lithuanian SSR in 1947–1957, especially the part of publications which were one way or another related to the Caucasus, has given us an incentive to conduct a deeper and broader investigation. The information about A. Vienuolis-Žukauskas and his traces left in the Caucasus during his youth was recorded and emphasized in the press during the Soviet period already, often implying at that point hidden intentions of soviet ideologists. However, a deeper insight in their content has revealed that this side of the writer’s biography is rather shadowy and there are many unanswered or deliberately veiled questions. Therefore, the article strives to attain two principal goals on the basis of the published and unpublished sources: 1) to disclose how the Caucasus is directly associated to the biography of A. Vienuolis-Žukauskas and what its influence was on the writer’s creative work in his youth and post-war period; 2) referring to the books dedicated to A. Vienuolis-Žukauskas by the Caucasian authors and to other publications related to the Caucasus from his memorial library to investigate when and how they were acquired, and to reveal the relationship between the writer and dedication authors. The research enabled us to reveal the less known or entirely unknown sides both of the biography of A. Vienuolis-Žukauskas and of his creation, as well as to correct certain fallacious statements institutionalized in our historiography throughout several decades and finally to open the doors into his private space in the middle of the 40ies and 50ies. The collected sources and their interpretation evidenced that the Caucasus exerted a great influence upon his work and left a conspicuous impact upon all the creative path of the writer. It may be stated that this pathway started and was broken right in the Caucasus. Books brought by A. Vienuolis-Žukauskas from his travel in the Caucasian republics in post-war years may be considered as an integral part of his biography and witnesses of his friendship with different famous authors from the Caucasian republics. Today, a sheaf of eloquent congratulatory telegrams and letters to commemorate the 70th and 75th jubilees of the writer sent by the Union of Soviet Writers as well as by individual authors and now held in the Anykščiai Memorial Museum of Antanas Baranauskas and Antanas Vienuolis-Žukauskas displays his relations with the writers of the Caucasian and other republics too. Undoubtedly, A. Vienuolis-Žukauskas won the recognition and respect of the Caucasian authors namely by his legendary Caucasian legends translated into different languages.
Keywords: ...